2020
DOI: 10.1111/ctr.14104
|View full text |Cite
|
Sign up to set email alerts
|

The structural conundrum of parolees and kidney transplantation

Abstract: In the United States, there are a large number of incarcerated individuals, resulting in high numbers of previously incarcerated individuals out on parole-who will be referred to as parolees in this paper-undergoing reentry into society. In 2016, this translated to 2640 per 100 000 adult residents in the United States being under correctional supervision, or roughly 1 in every 38 adults. 1 An aging prison population translates to an older parolee population, which translates to increased incidence of kidney di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…[28] Despite openly acknowledging the biases introduced by the use of social support, more than two thirds of the providers also agreed that patients with inadequate social support should be evaluated less favorably than those with social support. Although the Stanford Integrated Psychosocial Assessment for Transplant sought to incorporate objective measures of social support, [30] follow-up studies found that it specifically disadvantaged recently incarcerated patients, [31] patients insured through Medicaid, [32] and those of low socioeconomic status or with less than a high school education. [33] Importantly, meta-analyses find that social support is weakly and inconsistently associated with improved posttransplant outcomes.…”
Section: Nonmedical Criteria: Social Supportmentioning
confidence: 99%
“…[28] Despite openly acknowledging the biases introduced by the use of social support, more than two thirds of the providers also agreed that patients with inadequate social support should be evaluated less favorably than those with social support. Although the Stanford Integrated Psychosocial Assessment for Transplant sought to incorporate objective measures of social support, [30] follow-up studies found that it specifically disadvantaged recently incarcerated patients, [31] patients insured through Medicaid, [32] and those of low socioeconomic status or with less than a high school education. [33] Importantly, meta-analyses find that social support is weakly and inconsistently associated with improved posttransplant outcomes.…”
Section: Nonmedical Criteria: Social Supportmentioning
confidence: 99%
“…Others have argued for the need to make transplantation available to parolees (46). Ahmad and Eves (46) note in a recent article that although prisoners have a constitutional right to health care on the basis of the 1976 US Supreme Court ruling in Estelle v. Gamble (47), free (nonimprisoned) persons enjoy no such right under the Constitution. They argue that transplant centers and health care professionals have an ethical duty “to attend to the needs of parolees as a class.” Although Rhode Island Hospital is one of the centers that does not transplant prisoners while they are in prison, it has successfully listed and transplanted several people after they were released from the state prison.…”
Section: Ckd Among the Criminal Justice–involved Populationmentioning
confidence: 99%
“…Although the authors argued that a kidney transplant program for prisoners can be successful, they noted the need for better long-term follow-up of transplant recipients. Others have argued for the need to make transplantation available to parolees (46). Ahmad and Eves (46) note in a recent article that although prisoners have a constitutional right to health care on the basis of the 1976 US Supreme Court ruling in Estelle v. Gamble (47), free (nonimprisoned) persons enjoy no such right under the Constitution.…”
Section: Ckd Among the Criminal Justice-involved Populationmentioning
confidence: 99%